EFFECT OF FEEDING UREA ON DIGESTIBILITY, BEHAVIOUR, PLASMA UREA NITROGEN, AND GROWTH PERFORMANCE OF WEANED HOLSTEIN DAIRY CALVES - Rafay Ahmed Khan; Muhammad Tariq Javed; Arooj Fatima; Muhammad Zahid Iqbal; Saima Naveed; Muhammad Naveed-Ul-Haque; Khalid Abdul Majeed; Muhammad Ahmad; Nisar Ahmad; Ghazanfar Ali Chishti (Journal of Animal and Plant Sciences, 2025)
The objective of the study was to evaluate the effect of urea addition in the diet of recently weaned dairy calves on their digestibility, behaviour, plasma urea nitrogen and growth performance. Sixteen (female=10, average body weight=63.01 kg; male=6, average body weight=66.47kg), 8-week-old Holstein-Friesian weaned calves were randomly assigned to treatment groups A and B (n=8/trt). The calves in group A served as control and in group B, they were fed a diet of 0.5% urea inclusion from 9-12 weeks of age and 1.0% urea from 13-16 weeks of age. All calves were housed and fed individually in cages. Feed intake and behavioural observationswere recorded daily. Body measurements like heart girth, wither height, hip width, and hip height were measured at 8, 12, and 16 weeks of age. Blood samples were collected at 10, 12, and 14 weeks of age to measure Plasma Urea Nitrogen (PUN). All calves were weighed weekly to determine the average daily gain.The study found no negative effect of urea inclusion on calves' average daily gain, routine behavioral parameters, and growth performance. Similarly, urea inclusion did not negatively affect body weight, dry matter intake, or feed efficiency. However, it increased dry matter intake (DMI) digestibility in weaned dairy calves by 10.4%. The digestibility of non-fiber carbohydrates was 3.5% greater in calves fed urea-included diets. This study provides evidence that urea can be added to the ration of weaned dairy calves from the 8th week of age.
Keywords: Digestibility; Growth; Urea; Calves